Design, optimization, fabrication and analysis of Cu microheater for loop-mediated isothermal amplification (LAMP) applications - Ezhilnavaroji, Jeroish Zachariah; Bhuvaneshwari, K. S.; Futane, Abhishek; Fahmi, Samsuri; Narayanamurthy, Vigneswaran (Elsevier, 2023)
A paper presents the design, fabrication, and thermal evaluation of a printed circuit board (PCB) based copper (Cu) microheater that can be integrated with microfluidic chips to initiate the loop-mediated isothermal amplification (LAMP). A series of 3D finite element electro-thermal simulations were carried out to analyze the thermal uniformity and power consumption of the micro heater. The optimal design was fabricated using the etching technique and analyzed with a heat spreader to enhance thermal uniformity. The simulation results of the microheater reveal that the meander configuration outperforms other designs. In addition, the microheater with a heat spreader has a thermal difference of only < 5 ℃ when compared with ∼10 ℃ in a microheater without a heat spreader. The developed microheater has a long shelf life and can be used to handle wet biological samples when encapsulated with polyethylene terephthalate (PET). The paper microfluidic chip on the glass substrate has a temperature difference of only 0.5 ℃. The low-cost microheater integrated microfluidic chips has the great potential to develop inexpensive home-based diagnostic kits and trigger the access of diagnostic kits in underdeveloped countries to reduce the spread of infection and initiate treatment plans.